ACCURATE SENTINEL-2 INTER-BAND TIME DELAYS - R. Binet; E. Bergsma; V. Poulain (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Accurate knowledge on the time-delays between detector bands is paramount for the observation of dynamic features in Sentinel-2 imagery. Sentinel-2 inter-band time delays have been characterised analytically and empirically on Level-1B images with help of the rigorous geometric model. Two major contributors have been identified: optical distortion and satellite altitude inducing across- track and along-track delay variations up to ±2% with respect to ESA handbook fixed value. A harmonic attitude perturbation induces a 0.15% peak to peak temporal modulation on delays. An original method is proposed in order to estimate inter-band delays from L1C orthorectified and tiled products. The method relies on the orbital ephemeris embedded in L1C metadata and a lookup table. The performance assessment exhibits a maximum error of 1% and a rms error of 0.28%.